Optimization of extraction with salicylic acid, rheological behavior and antiproliferative activity of pectin from Citrus sinensis peels - Haj Romdhane, Mariem; Beltifa, Asma; Mzoughi, Zeineb; Rihouey, Christophe; Ben Mansour, Hedi; Majdoub, Hatem; Le Cerf, Didier (International journal of biological macromolecules, 2020)
A Box-Behnken design was used to optimize extraction temperature, extraction time and concentration of the salicylic acid to obtain a maximum polysaccharide yield from Citrus sinensis peels. The optimal settings were: extraction time 3 h, extraction temperature 80 °C and concentration of the salicylic acid 1.5%. Under these conditions, the experimental yield and uronic acid content were 11.74% and 66.9% respectively. Preliminary characterization was performed via FT-IR, SEC/MALS/VD/DRI and GC–MS after hydrolysis. SEC analysis showed that the extracted polysaccharide had a weight average molar mass of 350 kDa and an intrinsic viscosity of 640 mL/g. The GC–MS results revealed that the extracted polysaccharide was composed of arabinose 56.7%, galactose 17.8%, xylose 13.8%, rhamnose 5.1%, mannose 2.5% and glucose 1.5% suggested a rhamnogalacturonan pectin type I with a degree of esterification of 50.9% (IRTF). The flow curve and the dynamic frequency sweep were obtained at 10, 20, 30 and 40 g/L in water and at 30 g/L in presence of CaCl2 or NaCl at 1 mol/L. The solutions showed shear-thinning behavior fitted with Ostwald-De Waele model, except 10 g/L with a Newtonian behavior. The apparent viscosity and, the G’ and G” moduli increase with PACO concentration in agreement with a slow-down of the dynamic chain. In the presence of CaCl2 or NaCl the reduction of electrostatic repulsions between pectin chains decreases the rheological parameters. The effect is less sensitive with CaCl2 due to intermolecular interactions. The antiproliferative activity of the extracted pectin on human Caco-2 and Hep-2 cells was very interesting with an IC50 1.4 and 1.8 μg/mL respectively.